A pentacene thin film transistor with good performance using sol-gel derived SiO2 gate dielectric layer - Cavas, M.; Al-Ghamdi, Ahmed A.; Al-Hartomy, O. A.; El-Tantawy, F.; Yakuphanoğlu, Fahrettin (Elsevier, 2013)
A low-voltage pentacene field-effect transistor with sol-gel derived SiO2 gate dielectric was fabricated. The mobility of the transistor was achieved as high as 1.526 cm(2)/V on the bared SiO2/Si substrate by a higher dielectric constant. The interface state density for the transistor was found to vary from 3.8 x 10(10) to 7.5 x 10(10) eV(-1) cm(-2) at frequency range of 100 kHz-1 MHz. It is evaluated that the SiO2 derived by low cost sol-gel is quite a promising candidate as a gate dielectric layer for low-voltage pentacene field-effect transistor. (c) 2012 Elsevier Masson SAS. All rights reserved.
Keywords: Thin film transistor; Pentacene; Sol gel method